Penentuan Tingkat Kerusakan Lahan pada Berbagai Bentuk Penggunaan Lahan di Daerah Gumelar, Kabupaten Banyumas Jawa Tengah - Prasmaji Prasmaji; Ruly Eko Kusuma; Suwardi Suwardi; Prihastuti Prihastuti (Soilrens, 2018)
Land degradation represents a form of land productivity decrease that occurs due to the presence of incompatible land usage with land characteristic, which resulted in land capacity deterioration. Land degradation evaluation is determined based on Government Regulation No.150/2000 regarding land degradation control for biomass production, and Living Environment Minister Regulation No. 7/2006 for criteria standardization on soil measurement of biomass production. This research was conducted to evaluate land degradation levels based on physical characteristics of several land use patterns in Gumelar Region. The research used a survey method with homogenous land unit (HLU). HLU approaches were obtained from overlay between land use map and slope map. The measured parameters were i.e. solum thickness, surface rockiness, soil texture, bulk density, porosity and permeability. Results of the samples analysis were compared with the parameters values on Goverment Regulation No. 150/2000. The results of the research showed 69,7% of the total area of Gumelar had undergone land degradation. Garden land use contributed 51.5% land degradation, which was divided into several classes i.e. good and slight damage potential was 12.0%, slightly damaged was 17.7%, slightly damaged with damage potential was 4.8%, and damaged was 17.1%. Dry land contributed to damaged land degradation of 11.3%, and categorized entirely as slightly damaged, while the shrub land use contributes 6.9% of degraded land (with 2.8% and 4.1% were good with slight damage potential and slightly damaged with damage potential, respectively). Largest contribution of land damage towards land degradation was dry land, all dry land in study area were in slightly damaged condition. Garden was the land use with lowest land degradation, which indicates the most suitable land use in the studied area was garden.  Keywords:  land use, land degradation, homogenous land unit, overlay